2018
DOI: 10.1186/s13065-018-0434-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of oral bioavailability of doxorubicin through surface modified biodegradable polymeric nanoparticles

Abstract: BackgroundDoxorubicin hydrochloride (DOX·HCl), an anthracycline glycoside antibiotic, exhibits low oral bioavailability due to active efflux from intestinal P-glycoprotein receptors. The oral administration of DOX remains a challenge hence; no oral formulation for DOX is marketed, till date.Aim of the studyTo improve the oral bioavailability of DOX through, preparation of a nanoformulation i.e. PEGylated-doxorubicin(DOX)-loaded-poly-lactic-co-glycolic acid (PLGA)-Nanoparticles (NPs) and to develop and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 58 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…The EE and LE of the nanospheres were determined (Yang et al, 2017). The nanospheres were characterized using FTIR (Abbas et al, 2018;Dong et al, 2018), electron microscopy (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018), and laser particle size analysis (Couvreur et al, 2002;Zhang et al, 2015;Shi et al, 2016;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018). The results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EE and LE of the nanospheres were determined (Yang et al, 2017). The nanospheres were characterized using FTIR (Abbas et al, 2018;Dong et al, 2018), electron microscopy (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018), and laser particle size analysis (Couvreur et al, 2002;Zhang et al, 2015;Shi et al, 2016;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018). The results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Nanospheres morphology was observed using a transmission electron microscope (Shi et al, 2016;Nantachit et al, 2017;Tao et al, 2018). Zeta potential (surface charge) and particle size (nanospheres size) were measured using a laser particle size analyzer at 25°C (Zhang et al, 2015;Ahmad et al, 2018;Panchu et al, 2018;von Halling Laier et al, 2018).…”
Section: Synthesis Of C-pc/cmc-cd55sp Nanospheresmentioning
confidence: 99%
“…The use of these polymeric NPs can provide improvements in cancer therapy by exploring new routes of administration of some drugs, combining some active substances to potentiate their action or combining with other therapies like gene therapy. Ahmad et al [ 136 ] proposed an enhancement of doxorubicin oral bioavailability through surface modified biodegradable polymeric NPs as an alternative to intravenous administration. They studied drug-loaded PEGylated PLGA NPs pharmacokinetics compared to doxorubicin in Wistar rats.…”
Section: Polymeric Nanoparticles In Oncologic Treatmentmentioning
confidence: 99%
“…In the PEGylated doxorubicin (DOX) loaded PLGA-Nanoparticles (PEGylated-DOX-PLGA-NPs) observed a 6.8-fold oral bioavailability as compared to DOX-S in pharmacokinetics studies. 68 In addition, Feeney et al 69 modified lipid nanoparticles (LN) by using carrier materials of hydrogenated castor oil (HCO) and castor oil (CO) (containing PEG groups). They found that the relative bioavailability (defined as the ratio of AUC 0-∞ for the modified LN and its structurally analogous LN) of the formulations was 120% and 182% for HCO and CO formulations, respectively.…”
Section: Pegylated Drug Delivery Vehiclesmentioning
confidence: 99%